Marginalisation in China : Perspectives on Transition and Globalisation. - Zhang, Heather Xiaoquan (Marginal Regions (and in Association with IGU - Dynamics of Marginal and Critical Regions), 2007)
Economic transition in China has witnessed (re)centralization of resources from the margin to the core in economic, social and political senses. This book employs a marginalization lens to reveal, delineate and better understand the processes, patterns, trends, multiple dimensions and dynamics of the phenomenon, and the consequences and implications for development and well-being in the country.